Technological evolution of in vitro mock circulatory loops for advanced cardiovascular assist device evaluation - Li, Hongyu; Wang, Yiwen; Wu, Xuefeng; Zhou, Lijie; Liu, Lijia (Frontiers in Physiology, 2025)
The clinical reliability of implantable cardiovascular assist devices (CADs) necessitates rigorous verification by the Mock Circulatory Loop (MCL) to assess their hemodynamic performance, encompassing key parameters such as head, flow, and hemolytic properties. In this paper, we undertake a systematic review of the evolution of this technology system and propose a three-level classification model based on bibliometric analysis (n = 130), in which the dual-circulatory system accounts for 47.27% of the total, to reveal its physiological synergistic mechanism and the innovative application of multi-circulatory configurations in complex clinical scenarios. The study indicates that the prevailing technological impediments pertain to: (i) deviation of 3D-printed vascular mechanical properties (anatomical fidelity loss), (ii) decline in long-term shear force simulation accuracy, and (iii) paucity of module interface compatibility. From an interdisciplinary integration perspective, the present study indicates that adaptive closed-loop hybrid-MCL systems represent a key direction for technological evolution: their architecture, which couples real-time digital twins with physical loops, can dynamically adjust blood flow parameters. When combined with multi-scale simulation optimization, this approach significantly enhances the reliability of long-term shear stress predictions. Furthermore, the integration of personalized digital twins establishes a high-fidelity patient-specific validation platform, thereby providing a theoretical framework for precise evaluation of cardiovascular devices.